Congruence of the topography of intracranial calcifications and epileptic foci - A. Cukiert; P. Puglia; H.B. Scapolan; M.M. Vilela; R. Marino Jr (Arquivos de Neuro-Psiquiatria)
Nodular intracranial calcifications (NIC) are frequent findings in CT scans of epileptic patients in countries where granulomatous central nervous disease such as neurocysticercosis is endemic. In 34 consecutive epileptic patients with NIC submitted teo EEG, CT and CSF analysis, the correlation between the electroclinical localization of the focus and the topography of the NIC was studied. Twenty-nine patients had partial (Group I) and 5 had primarily generalized seizures (Group II). Twenty group I and 1 group II patients showed abnormal EEGs. CSF abnormalities consisted of increased protein content (n=3) and positive Weinberg's reaction (n=2). In 2 cases, viable neurocysticercotic vesicles were seen. Twenty-one patients had single NICs. No correlation could be stablished in group II patients. Within group 1,15 patients had a positive and 14 a negative correlation. Sixty-six percent of the patients with single NICs had negative correlations. These findings strongly suggest that the calcifications themselves are not the epileptogenic lesions in at least 50% of the studied cases.